The Applications of Building Information Modelling in Facilities Management - Olatunji, Oluwole; Sher, W. (IGI Global: Information Science Reference, 2010)
Effective processes in facilities management are responsive to the quality of information flow across various levels and stages of design, procurement and construction processes. Considerable empirical evidence from industry reports shows how construction and facilities management processes could be jeopardized by some of the limitations of conventional design and procurement processes. To address these limitations, there are promising indications showing that the potential of Building Information Modelling (BIM) will trigger major improvements in both construction and facilities management systems. This study reviews some of the capabilities of BIM which may revolutionize conventional practices in facilities management processes. Specific platforms for this include, integrated analysis and simulation of project variables in virtual environments, effective communication between project stakeholders and project teams and multi-disciplinary collaboration. Others are interoperability, project visualization, value intelligence and other digital facilities management applications. In the study it is argued that BIM capabilities such as project visualization, simulation, auto-alert and value intelligence could stimulate major improvements in facilities management processes. Finally conclusions are drawn on the relationships between BIM and digital facilities management, including suggestions on areas of further studies.